Improved forages and milk production in East Africa. A case study in the series: Economic foresight for understanding the role of investments in agriculture for the global food system - Gonzáles, Carlos; Schiek, Benjamin E.; Mwendia, Solomon W.; Prager, Steven D. (International Center for Tropical Agriculture, 2016)
Production of livestock and dairy products in Sub-Saharan Africa has not kept pace with growing demand. The potential exists to close this gap in a climate-friendly way through the introduction of improved forage varieties of the Brachiaria genus. We assess the potential economic impact of the development and release of such varieties in six East African countries using an economic surplus model. Results are presented across a range of potential scenarios involving different adoption rates and percentage increases in productivity. For all but the lowest levels of adoption and productivity increases, improved forages have the potential for positive return on investment. Using these results, we present formulae that help readers calculate the adoption rate or percentage increase in productivity necessary to achieve specific desired levels of net benefit. Overall, the model output suggests that investment in a forages research program related to both the qualities of the forage itself as well as programs to enhance dissemination and adoption of new materials would be low risk and with high likelihood for positive outcome, generating discounted net benefits on the order of potentially tens of millions of dollars.